Statistics for prey size (mean (SE) and maximum size, mm) of food items in gizzards of eiders separated into eight categories: Blue mussel Mytilus edulis , cockle Cerastoderma edule , razor clam Ensis directus , bivalve spp., periwinkle Littorina littorea , draft whelk Hinia reticulata , conch Buccinum undatum and shore crab Carcinus maenas . - Karsten Laursen (556576); Anders Pape Møller (7913618) (2021)
Statistics for prey size (mean (SE) and maximum size, mm) of food items in gizzards of eiders separated into eight categories: Blue mussel Mytilus edulis , cockle Cerastoderma edule , razor clam Ensis directus , bivalve spp., periwinkle Littorina littorea , draft whelk Hinia reticulata , conch Buccinum undatum and shore crab Carcinus maenas .